Pengaruh variasi pembagian jumlah anoda dengan pola horisontal terhadap laju korosi baja SS400 pada media air laut - Faisol, A.; Sumarji, S.; Djatisukamto, G. (Dinamika Teknik Mesin, 2018)
Sacrificial anode protection is one type of corrosion protection used to inhibit corrosion rate. The sacrificial anode protection works by utilizing the potential difference between anode and cathode. This research aims to determine the effect of variation in the distribution of quantities and distribution of sacrificial anode aluminum to SS400 steel corrosion rate. The method of calculating the corrosion rate used is the weight loss test. The results of this test indicate that the more uniform distribution of the anode on the surface of the cathode the better the resulting protection will be. The best protection is produced by 4 pieces of sacrificial anode size of 0,5 x 4 cm with an average rate of corrosion rate of 0,1067 mm/year. Protection with 2 pieces of sacrificial anode size 1 x 4 cm resulted in corrosion rate with average value 0,1462 mm/year, while on protection of 1 victim anode with size 2 x 4 cm can produce protection with average value of corrosion rate 0,1677 mm/year. Equivalent distribution of numbers and distributed anodes can narrow the distance between the anodes so that the value of the material's resitivity is smaller and the electrons can be distributed evenly over the entire cathode surface.The corrosion that occurs in SS400 steel is a kind of uniform corrosion. It is seen from the size of the cavity that occurs on each side of the specimen after the immersion process.